(untitled) (Teacher Education through Flexible Learning in Africa (TETFLE), 2022)
COVID-19 was declared a pandemic on 11 March 2020. Various governments introduced measures to mitigate the pandemic, including lockdown, enforced compliance with social distancing, travel restrictions, a ban on large meetings and the closure of schools. At the peak of the epidemic, learning centres and higher institutions were closed in more than 190 countries, disrupting the education of 1.6 billion students. In Nigeria, this situation forced many schools, including universities, to introduce e-learning. This study, which explores the extent to which selected students at the University of Lagos were adequately prepared for e-learning, was based on the Garrison and Anderson Community of Inquiry model. An analytical survey research design was adopted and a stratified random sampling technique was used to select 282 respondents from the University of Lagos. A validated self-developed questionnaire was used for data collection. Frequencies, percentages and means were calculated. Hypotheses were statistically tested at a 5% level of significance. The study found that the students in the Faculty of Education were to some extent prepared for the teaching mode, and they were assisted to establish social and cognitive presences to create a meaningful e-learning environment.